Unamuno's conception of subject area as a living science - Maroco dos Santos, Emanuel José (2017)
For Unamuno, who envisaged the professor as a forger of doctrines, the university subject, standing at the antipodes of his conception in secondary education, should be an expression of a living or in fieri science, not a repository of knowledge. With this stance, this author eventually opposed the official science and scientific dogma in favour of teaching procedures. The current paper seeks to recover this conception of course (subject), while trying to unveil such conception in its various dimensions, with an ultimate purpose of bringing into the space of the contemporary pedagogical reflection the sui generis educational ideas of Unamuno, which allow to prospect the subject area not only as a place of simple instruction but as a moment of investigation of "hypotheses and utopias". The methodology that we shall be using in this research study is reading, analysis and commentary of Unamuno’s texts. Their philosophical, educational and historical contextualization is carried out based on Unamuno’s opposition, within his work, to scholastic pedagogy, which was present in the university of his time in the figure of the university professor or reader. Unamuno’s proposition is that the teacher and the student lose their classic characteristics which define them as “house of knowledge” and “empty container”, respectively, in favour of a conception more adapted to the new academic times, in which the continuous scientific and cultural development makes obsolete the contents assimilated yesterday.